Genome Dynamics and Stability
DOI: 10.1007/7050_2007_026
|View full text |Cite
|
Sign up to set email alerts
|

Spo11 and the Formation of DNA Double-Strand Breaks in Meiosis

Abstract: Meiotic recombination is carried out through a specialized pathway for the formation and repair of DNA double-strand breaks made by the Spo11 protein, a relative of archaeal topoisomerase VI. This review summarizes recent studies that provide insight to the mechanism of DNA cleavage by Spo11, functional interactions of Spo11 with other proteins required for break formation, mechanisms that control the timing of recombination initiation, and evolutionary conservation and divergence of these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
359
0
1

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(371 citation statements)
references
References 237 publications
(378 reference statements)
8
359
0
1
Order By: Relevance
“…Gonadal dysgenesis in Atm mice was initially thought to be caused by defects in meiotic recombination (30,34), which is induced by DSBs generated by the SPO11 protein (49). Consistent with our results in mouse somatic cells, however, recent studies have shown that ATM is not required for meiotic recombination, like when Spo11 gene dosage is reduced (50), but rather, that ATM plays an important role in regulating DSB levels during meiosis (51).…”
Section: Discussionsupporting
confidence: 90%
“…Gonadal dysgenesis in Atm mice was initially thought to be caused by defects in meiotic recombination (30,34), which is induced by DSBs generated by the SPO11 protein (49). Consistent with our results in mouse somatic cells, however, recent studies have shown that ATM is not required for meiotic recombination, like when Spo11 gene dosage is reduced (50), but rather, that ATM plays an important role in regulating DSB levels during meiosis (51).…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps because of this divergence, we have been unable to identify clear homologs of these proteins in most organisms other than those related to S. cerevisiae. Similar divergence is seen for the other meiosis-regulated DSB proteins Jiao et al 2002;Henderson et al 2006;Keeney 2007), but this feature is not unique to the DSB proteins, as it has been observed that meiotic recombination proteins in general tend to be among the most rapidly diverging groups of proteins in the cell (see Ramesh et al 2005;Richard et al 2005). …”
Section: Amino Acid Sequence Alignments Of Highly Diverged Yeast Mei4supporting
confidence: 59%
“…Rec114 and Mei4 are highly divergent. For example, in the very closely related species S. cerevisiae and S. paradoxus, Mei4 and Rec114 homologs share only 84.1% and 73.4% amino acid identity, respectively Keeney 2007). In contrast, the nucleotide sequence across all coding regions in these species is >88% identical and ∼65% of proteins have ≥90% amino acid identity (Cliften et al 2001).…”
Section: Amino Acid Sequence Alignments Of Highly Diverged Yeast Mei4mentioning
confidence: 99%
See 1 more Smart Citation
“…2 A). SPO11은 고세균 Topoisomerase VI의 상동체이며, 활성 중심 부위인 tyrosine 잔기 ester 전이 반응에 의해 DNA 가닥을 절단한다 (Keeney et al 1997;Keeney 2008). 또한 SPO11은 DNA 절단 후 DNA와 공유 결합된 상태로 남아있다 (Keeney et al 1997;Keeney, 2008 (Fig.…”
unclassified